Deformation and evolution of Aptian salt tectonics in the central Lower Congo Basin: integrated analogue and 3D discrete element modelling - Cheng, Peng; Qi, Yanxin; Zhao, Jiasen (Frontiers in Earth Science, 2025)
The Lower Congo Basin, a salt-rich passive-margin basin, displays complex coupling between salt tectonics and sedimentation that strongly controls hydrocarbon systems, yet the deformation mechanisms and spatiotemporal evolution of its Aptian salt structures remain insufficiently constrained. Here we combine basin-scale physical analogue experiments with structure-scale three-dimensional discrete element method (3D DEM) simulations to investigate the gravity-driven deformation and three-dimensional kinematics of salt structures in the central Lower Congo Basin. The analogue models reproduce seaward gravitational spreading of the Aptian salt and overburden followed by contraction triggered by delayed frontal obstruction against volcanic outer highs, whereas the 3D DEM experiments resolve salt–sediment coupling, strain partitioning and salt-flow anisotropy around pre-existing diapirs. The results define a three-phase evolutionary model for passive-margin salt tectonics: (1) a Global Extension phase dominated by salt-raft development and passive diapirism; (2) a Frontal Obstruction phase in which arrested downslope salt flow localizes compressional stresses; and (3) a Compression Propagation phase that produces squeezed and welded diapirs with mushroom and teardrop geometries and associated minibasins. Pre-existing diapirs function as preferential strain sinks and “stress-release windows” that focus velocity anomalies and control the migration of depocenters toward active diapirs, promoting minibasin asymmetry. Comparison with seismic profiles from the central Lower Congo Basin shows good agreement, supporting the predictive value of the models. These findings provide a three-dimensional mechanical framework for the evolution of salt-bearing passive margins and offer guidance for assessing structural controls on hydrocarbon trap development in salt-influenced basins.